Investigation of serum homocysteine levels in relation to age and sex - AKSOY, N.H. (Journal of the Hellenic Veterinary Medical Society, 2020)
Homocysteine is a non-proteinogenic and a derived amino acid in the methionine metabolism and is a risk factor for cardiovascular and many other metabolic diseases. In this study, the purpose was to determine serum homocysteine levels in healthy sheep based on differences in age and gender. 220 healthy Akkaraman sheep, composed of both females (n=55 lambs and 55 ewes) and males (n=55 lambs and 55 rams), were used as animal samples. The measurements of serum homocysteine concentrations were performed with ELISA-HCY kit. The levels of serum homocysteine of sheep were detected in ewes, female lambs, rams and male lambs as 2,91±0,50; 2,99±0,42; 11,22±3,10; 6,43±1,26 μmol/L, respectively. The primary intent of this study was to investigation and characterization the serum Hcy concentrations in healthy sheep broken down by different ages in both genders As a result, the serum homocysteine values that can constitute a reference value for healthy breeds of sheep were determined in this study.